An Analysis on Writing Materials of English Textbooks for Seventh Grade entitled “Bahasa Inggris When English Rings a Bell” Published by Ministry of Education and Culture - Fahmi, Iqbal Zulfikar (RETAIN, 2021)
The aim of this study is to identify the writing task presented on the textbook and the conformity to writing tasks criteria on English textbook for seventh grade published by Ministry of Education and Culture. This study used descriptive qualitative in terms of content analysis as the methodology. The data were obtained from textbook and checklist. The textbook is used to identify the presented writing task on the textbook and the checklist which were selected and adapted from BSNP and William (1983) is used whether the writing task on the textbook is conformed to the criteria or not. The result shows there were four types of writing tasks performed in the textbook; making list, filling in table, completing sentence, paragraph, or conversation, and reviewing. The writing tasks also conform to its criteria; giving them controlled and guided writing, has appropriate progression and variety tasks, dealing with writing components, and leading the written work to be practiced orally. Keywords: textbook, writing task, and criteria